Nasaruddin Umar: Tasawuf Wasathiyah dalam Masyarakat Modern - Rizki Maulana; Muhammad Iqbal Irham (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
This article aims to present an in-depth exploration of Wasathiyah Sufism, which is a form of modern Sufism, without simplifying or expanding its core ideas. Wasathiyah Sufism seeks to transform modern society that is rational, empirical, hedonistic, materialist, individualist, even secular into a pious, tolerant, high social spirit, and moral society without isolating oneself from society, the world, or the workplace. This Sufism helps humans develop objectivity, professionalism, and awareness of their duties, obligations and responsibilities as servants of Allah and messengers of Allah on earth which are very much needed by the people. This study uses a qualitative method to examines Nasaruddin Umar's thoughts supported by the literature in accordance with the topic of this study. The results of this study concluded that the method of getting closer to Allah through tasawuf wasathiyah is carried out by combining concern for the world with concern for the hereafter. The goal is to realize a virtuous social and spiritual order, this moderate idea (tawasuth) will give birth to a new model of contemporary society that is balanced (tawazun), proportional (i'tidal), and tolerant (tasamuh).Abstrak: Artikel ini bertujuan menyajikan penggalian mendalam atas tasawuf wasathiyah yang merupakan salah satu bentuk tasawuf modern, tanpa penyederhanaan atau perluasan gagasan intinya. Tasawuf Wasathiyah berupaya mengubah masyarakat modern yang rasional, empiris, hedonistik, materialis, individualis, bahkan sekuler menjadi masyarakat yang saleh, toleran, berjiwa sosial tinggi, dan bermoral tanpa mengisolasi diri dari masyarakat, dunia, atau tempat kerja. Tasawuf ini membantu manusia mengembangkan objektivitas, profesionalisme, dan kesadaran akan tugas, kewajiban, dan tanggung jawabnya sebagai hamba Allah dan utusan Allah di muka bumi yang sangat dibutuhkan oleh umat. Penelitian ini menggunakan metode kualitatif yang meneliti pemikiran Nasaruddin Umar dalam didukung dengan literatur-literatur kepustakaan sesuai dengan topik penelitian ini. Hasil penelitian ini menyimpulkan bahwa metode mendekatkan diri kepada Allah melalui tasawuf wasathiyah dilakukan dengan menggabungkan kepedulian terhadap dunia dengan kepedulian terhadap akhirat. Sasarannya adalah mewujudkan tatanan sosial dan spiritual yang berbudi luhur, gagasan moderat (tawasuth) ini akan melahirkan model baru masyarakat kontemporer yang seimbang (tawazun), proporsional (i'tidal), dan toleran (tasamuh).